Gravity or turbulence? – IV. Collapsing cores in out-of-virial disguise. Issue 2 (12th June 2018) - Ballesteros-Paredes, Javier; Vázquez-Semadeni, Enrique; Palau, Aina; Klessen, Ralf S
ABSTRACT: We study the dynamical state of massive cores by using a simple analytical model, an observational sample, and numerical simulations of collapsing massive cores. From the analytical model, we find that cores increase their column density and velocity dispersion as they collapse, resulting in a time evolution path in the Larson velocity dispersion-size diagram from large sizes and small velocity dispersions to small sizes and large velocity dispersions, while they tend to equipartition between gravity and kinetic energy. From the observational sample, we find that: (a) cores with substantially different column densities in the sample do not follow a Larson-like linewidth–size relation. Instead, cores with higher column densities tend to be located in the upper-left corner of the Larson velocity dispersion σ v, 3D –size R diagram, a result explained in the hierarchical and chaotic collapse scenario. (b) Cores appear to have overvirial values. Finally, our numerical simulations reproduce the behaviour predicted by the analytical model and depicted in the observational sample: collapsing cores evolve towards larger velocity dispersions and smaller sizes as they collapse and increase their column density. More importantly, however, they exhibit overvirial states. This apparent excess is due to the assumption that the gravitational energy is given by the energy of an isolated homogeneous sphere. However, such excess disappears when the gravitational energy is correctly calculated from the actual spatial mass distribution. We conclude that the observed energy budget of cores is consistent with their non-thermal motions being driven by their self-gravity and in the process of dynamical collapse.